2018
DOI: 10.1080/02699206.2018.1513565
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid morphological disorder apparent in some children aged 4-5 years with childhood apraxia of speech: findings from standardised testing

Abstract: There is continuing debate about the origins of productive morphological errors in children with speech sound disorders. This is the case for children with theorised phonetic and motor disorders, such as children with childhood apraxia of speech (CAS, e.g., Ekelman & Aram, 1983; McNeill & Gillon, 2013 ). The morphological skills of children with CAS remain relatively unexplored in pre-schoolers. We investigated English morphology in a retrospective, cross-sectional design of 26 children aged 4-5 years who comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 33 publications
6
19
0
Order By: Relevance
“…Rosenbek & Wertz, 1972). This gap has also been reported in a more recent study (Murray et al, 2019). In that study, morphological disorder was found in 48% of 4-5-year old children with CAS.…”
Section: Childhood Apraxia Of Speech Comorbiditysupporting
confidence: 64%
See 4 more Smart Citations
“…Rosenbek & Wertz, 1972). This gap has also been reported in a more recent study (Murray et al, 2019). In that study, morphological disorder was found in 48% of 4-5-year old children with CAS.…”
Section: Childhood Apraxia Of Speech Comorbiditysupporting
confidence: 64%
“…The reported gap between receptive and expressive language competence in children with CAS (e.g. Rosenbek & Wertz, 1972;Murray et al, 2019) was confirmed in study IV. The proportion of children having an expressive language disorder (67%) was similar to the reported proportions of Dutch and English-speaking children (46-82%) (Thoonen et al, 1997;Lewis et al, 2004;Iuzzini, 2012;Vuolo and Goffman, 2018;Zuk et al, 2018;Murray et al, 2019).…”
Section: A Language Profile Associated With Childhood Apraxia Of Speechsupporting
confidence: 52%
See 3 more Smart Citations